The Task-Based Evaluation of the English for Nusantara Textbook to Curriculum Merdeka Principles - Idris, Bayu Romli; Muamaroh, M; Ratih, Koesoema (Universitas Muhammadiyah Surakarta, 2025)
This study examines the tasks in English for Nusantara (Kementerian Pendidikan, 2022) based on the theme